(untitled) (Philadelphia, 2001)
(Hanley & Belfus) Wright State Univ., Dayton, OH. Presents a variety of concise patterns of symptoms, signs, and selected supplemental data occurring with various diseases. Each pattern is followed by the diagnosis and a short discussion of the pathophysiology and the key historical, physical, and laboratory findings accompanying the condition. Softcover. DNLM: Diagnostic Tech.
Keywords: Diagnosis,Chẩn đoán